The extracisternal approach in vestibular schwannoma surgery and facial nerve preservation - Vellutini, Eduardo A. S. (2014)
The classical surgical technique for the resection of vestibular schwannomas (VS) has emphasized the microsurgical anatomy of cranial nerves. We believe that the focus on preservation of the arachnoid membrane may serve as a safe guide for tumor removal. Method: the extracisternal approach is described in detail. We reviewed charts from 120 patients treated with this technique between 2006 and 2012. Surgical results were evaluated based on the extension of resection, tumor relapse, and facial nerve function. Results: Overall gross total resection was achieved in 81% of the patients. the overall postoperative facial nerve function House-Brackmann grades I-II at one year was 93%. There was no recurrence in 4.2 years mean follow up. Conclusion: the extracisternal technique differs from other surgical descriptions on the treatment of VS by not requiring the identification of the facial nerve, as long as we preserve the arachnoid envelope in the total circumference of the tumor.